Speed Control of Permanent Magnet Brushless DC Motor Using Fuzzy Logic Controller-Hardware Implementation (International Journal of Engineering and Computer Science, 2013)
BLDC motors are very popular and are replacing brush motors in numerous applications. Because the BLDC motor does not require commutator and due to its superior electrical and mechanical characteristics and its capability to operate in hazardous conditions it is more reliable than the DC motor. Traditionally, three-phase inverters are generally used to control these motors, requiring a rotor position sensor for starting and for providing the proper commutation sequence to stator windings. The disadvantages of sensored motor control system are increased cost and size of the motor, and need special mechanical arrangement for mounting the sensors. Another problem associated with BLDC motor control is the use of Conventional controllers; these controllers poses difficulties under the conditions of nonlinearity, load disturbances and parametric variations. This paper presents the design and implementation of a fuzzy logic controller for the sensorless speed control of brushless dc motors which will be helpful in solving problems associated with sensored control and conventional controllers in order to reduce cost and complexity of the drive system without compromising the performance